ETOS KERJA DINAS PENDIDIKAN KABUPATEN KEPULAUAN MENTAWAI - Elvina Taporuk (Universitas Negeri Padang, 2014)
The background of this research is the phenomenon that shows that Personnel Mentawai Islands Department of Education has not have good work ethic yet. This research is aimed to obtain the information about Work Ethics of the Mentawai Islands Department of Education Personnel in improving their work. The population is 50 Personnel of Mentawai Islands Department of Education. Data collection tool used was a questionnaire that had been tested for validity and reliability. So in general, the average score Personnel Work Ethics in Mentawai Islands Department of Education reach a score of 3.42 in the good category. Keywords: PersonnelWork Ethics